Telaah Divergensi Kepuasan Hidup Dalam Karakteristik Demografis, Performa Akademik, dan Spektrum Psikologis Mahasiswa - Rony Setiawan; Ariesya Aprillia (Jayapangus Press, 2023)
Students play an important role for the regeneration of the country's development in the future. The contribution and quality of graduates is largely determined by the maturity of the possessed way of thinking and displayed skills. Students need to have a positive mindset while in the learning cycle on campus. Valuable and enjoyable experiences during student life will make them optimistic, enthusiastic, proactive, and independent. This study aims to analyze life satisfaction with comparative factors, including demographic characteristics, academic achievement, and students’ personality who are still active at public and private universities in Bandung. This research was preceded by an empirical literature review and carried out using a snowball sampling survey and continued with an analysis of the feasibility of research instruments and data so that accurate, reliable, and comprehensive information can be obtained through ANOVA analysis and descriptive statistics. Research conducted has proven that there are differences in the level of student satisfaction based on the presence of parents, organizational activity, and their personality. These results are expected to be useful input, especially for the managers of each university to be more concerned about paying attention, observing, understanding, and participating in improving, maintaining, and improving the quality of life lived by the students as a reflection of responsible service in individual, group, and institutional scope.